(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Health education communication plays an important role in contributing to improving treatment effectiveness, experience and satisfaction of patients and family members. Objective: Describe health education communication activities for inpatients at Thu Duc City Hospital in 2024 and related factors. Results: 100% of patients received individual consultation, 36.3% of patients received group consultation, 76.7% of patients received indirect communication, including: Communication via website/fanpage: 46%, documents wall prints: 63.3%, digital video images: 47.4% and handheld printed documents: 52.1%. The patient’s gender and age group are related to the ability to access indirect communication channels; The communication skills of medical staff are related to the positive response rate of patients regarding personal consultation. Conclusion: 100% of patients received direct communication, 76.7% received indirect communication. Some factors related to the ability to access indirect communication channels are gender and age group, communication skills of medical staff are related to the rate of positive feedback from patients about this form of consultation. personal consultation